Microspherophakia in a 47, XYY Syndrome Patient: A Case Report - Maria Lourdes Rubalcava-Soberanis; Bani Antonio-Aguirre; Cristina Mendoza Velásquez; Andric Christopher Perez-Ortiz; Claudia Palacio-Pastrana (Case Reports in Ophthalmology, 2020)
47, XYY syndrome affects males with variable phenotypic expression. Around 80–99% of affected individuals present low-set ears, malar flattening, motor delay, and tall stature. Yet, some cases lack signs or symptoms or are barely noticeable. There are four reports of ocular involvement among these individuals – one with unusual multiple retinal atrophic holes in the posterior pole, other with coloboma, an association with morning glory syndrome, and a case of congenital cataract. Here, we describe a plausible new ocular sign in a 4-year-old male with 47, XYY syndrome who was brought to the outpatient clinic for vision loss. After a complete assessment, we diagnosed a right-sided phacomorphic glaucoma and microspherophakia treated with phacoemulsification and aspiration with posterior capsulotomy and anterior vitrectomy, followed by an Ahmed valve implant for intraocular pressure control. Even though there is a low prevalence of ocular involvement in 47, XYY syndrome cases, this might reflect the rarity of the full expression of the disease leading to an underdiagnosis, added to the scarcity of cases. Microspherophakia and phacomorphic glaucoma among four others previously reported ocular findings could be looked for in 47, XYY syndrome patients.